Mecanismos de defesa vegetal e controle de Meloidogyne incognita por formulado alecrim em hidrogel em tomateiro - Schons , Bruna Caroline (2020)
Tomato is a susceptible plant to damage caused by various diseases, including Meloidogyne incognita that stands out causing losses in production and having a difficult control. Seeking for effective ways to solve this problem, the objective of this work was to develop an alternative method through the use of rosemary extract (Rosmarinus officinalis) in formulation with the hydrogel, as a delivery vehicle. For this purpose, an in vitro motility and mortality experiment was carried out at concentrations of 1%, 3%, 5% and 10% of the pure rosemary extract. An evaluation was carried out after 24 hours of contact with the treatments (motility). Replacement of treatments with water and an evaluation was carried out at 48 hours (mortality). To verify the effectiveness of this control in a similar situation to the field, an experiment was carried out in a greenhouse with tomatoes of the Santa Clara variety, with treatments 0.25; 0.50; 0.75; 1.00 and 1.25 g of the formulated, where the control corresponded to 1.25 g of hydrogel without the addition of extract and an absolute control containing only water. The variables analyzed were: quantity of egg masses (EM); total number of galls; total number of nematodes per root; number of nematodes per gram of root (N g-1 root); reproduction Factor. To verify if the control obtained by the formulated was from resistance induction, a new experiment was carried out using the doses tested previously, where root samples were collected in triplicate at times 0, 5, 10, 20 and 50 days after inoculation, and the inoculation was performed 3 days after the contact of the plants with the treatment. The activity of the enzymes Phenylalanine ammonia-lyase (PAL), Peroxidase (POX), Polyphenoloxidase (PFO) was measured by direct spectrophotometry. The result of in vitro experiment show the immobility of 100% of juveniles of M.incognita was found at the calculated dose of 1.5% and 100% of mortality at the calculated dose of 4.5%. All nematologics variables show the same behavior, where it was found the proportional reduction to the dose increase, showing that the control was effective. In enzymes, FAL showed no statistical difference in any treatment and in any time tested. POX and PFO, on the other hand, showed peaks of different treatments at different times, highlighting the treatment of 1.25 g of the formulated product, which may be an indication of resistance induction.